Expert Appraisal on Islamic Textual Enhancement Grammar Book Designed for Grammar Teaching At IAIN Bukittinggi - Veni Roza; Genta Sakti (Jurnal Educative: Journal of Educational Studies, 2018)
The article aims at evaluating of grammar book designed by the author from some experts.  Experts’ appraisals were needed to judge whether Textual Enhancement model designed for teaching grammar at IAIN Bukittinggi was valid or not. In this model, the researcher designed grammar lesson of complex sentences under the model of textual enhancement. She made salient grammar features taught by giving boldfaces and colors in every appearance of complex sentences within the texts in order to draw students’ attention to notice it. The study is mixed methods of quantitative and qualitative. Questionnaire and interview were used to collect data of expert judgments on the model developed (grammar book). There are five experts involved in this research who evaluate the book with impressionistic method which includes language, content and organization. The finding reveals that textual enhancement grammar book is valid and reliable. It can be used after being revised in the aspect of language with some grammar and spelling errors, in the aspect of content to suit with native culture, and organization, to consider the attractive sense.  Artikel ini bertujuan untuk mengevaluasi buku Grammar yang dirancang oleh Penulis sendiri dari  beberapa orang pakar.  Penilaian pakar sangat dibutuhkan untuk melihat validitas dan reliabilitas buku model yang dikembangkan sebelum diterapkan dalam pengajaran Grammar di Program Studi Pendidikan Bahasa Inggris IAIN Bukuttinggi. Dalam model ini, penulis merancang pelajaran Grammar dengan topik Complex Sentences dengan penguatan teks di bawah tema-tema Islam dengan memberikan cetak tebal dan pewarnaan pada fitur Grammar yang diajarkan untuk menarik perhatian mahasiswa memikirkannya. Jenis penelitian ini adalah penelitian campuran kuantitatif dan kualitatif.  Angket dan wawancara digunakan untuk mengumpulkan data terkait penilaian pakar terhadap buku yang dirancang. Ada lima pakar yang terlibat yang menilai aspek bahasa, isi, organisasi buku. Temuan menunjukkan buku grammar yang dirancang memenuhi kriteria valid dan  reliable. Buku dapat digunakan setelah direvisi pada beberapa aspek kesalahan grammar dan ejaan, aspek isi untuk mencocokkan dengan budaya asli (arab) dan aspek oragnisasi buku untuk memperhatikan daya tarik buku.